2020
DOI: 10.3390/polym12071483
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Affects Activated Carbon from Piassava

Abstract: The specificity of activated carbon (AC) can be targeted by pretreatment of the precursors and/or activation conditions. Piassava (Leopoldinia piassaba and Attalea funifera Martius) are fibrous palms used to make brushes, and other products. Consolidated harvest and production residues provide economic feasibility for producing AC, a value-added product from forest and industrial residues. Corona electrical discharge and extraction pretreatments prior to AC activation were investigated to determine ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Carbon content between 58.7 and 75.7% were obtained for activated carbon with CO 2 that was prepared from black wattle bark [ 50 ]. Piassava fiber was used for the preparation of activated carbon with CO 2 , the authors found a carbon content between 82.03 and 13.53% for oxygen [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon content between 58.7 and 75.7% were obtained for activated carbon with CO 2 that was prepared from black wattle bark [ 50 ]. Piassava fiber was used for the preparation of activated carbon with CO 2 , the authors found a carbon content between 82.03 and 13.53% for oxygen [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the manufacturing process, the fibers are cut to a standard length, and those shorter are discarded and become disposable waste. These piassava fiber wastes have limited commercial use and are normally burned [37]. As an alternative, this fibrous waste can be further processed and ground to powder to be incorporated into polymer composites.…”
Section: Requirementsmentioning
confidence: 99%
“…It is important to note that the chemical characterization of dried and not dried pretreated pulps was the same because alkaline pretreatments of the cellulosic pulps were the same in both cases. It is clear that all chemical pretreatments performed resulted in a relative increase of the glucose content as a probable consequence of the decreased content of hemicellulose, mainly xylose (Castro et al 2020). The higher the NaOH concentration and pretreatment time of the fibers were, the greater the relative amount of cellulose and lower the xylose content (Bufalino et al 2015).…”
Section: Chemical Characterization Of the Pulpsmentioning
confidence: 99%